Rest Area Development in Central Java (Case Study: Rest Area on Semarang–Solo Toll Road) - Darmawan, Edy; Sari, Suzanna; Werdiningsih, Hermin; Enis, Adhisti (Unijourn Publisher, 2021)
The construction of the road network is carried out to support the growth and acceleration of the economic process and the development of the tourism industry. It is also projected to improve the socio-economic conditions of the community. In the last few years, the Central Java Government has built toll roads to connect several cities in Central Java in one fast lane. However, it was not followed by the construction of supporting facilities such as rest area that serves a place to rest for motorists when they experience fatigue during long trips. The existence of the place is still limited, and it was not evenly distributed along the toll road, causing long queues at the entrance of some rest area when the volume of the vehicles is overflow. Based on these problems, the purpose of this research is to study and develop the requirement of rest area that can meet the needs of motorists traveling through the toll roads in Central Java. To achieve these objectives, this research used a qualitative descriptive method to describe and explain the problems in the field, and further analyze them to get a comprehensive result. The result of this research is presented in the form of published research reports and scientific articles. It is expected to provide benefits to the relevant scientific field, especially those related to architecture in developing rest areas that suit the needs of road users.